A novel nomogram for adult primary perihilar cholangiocarcinoma and considerations concerning lymph node dissection - Zhang, Qi; Liu, Zehan; Liu, Shuangqing; Wang, Ming; Li, Xinye; Xun, Jing; Wang, Xiangyu; Yang, Qin; Wang, Ximo; Zhang, Dapeng (Frontiers in Surgery, 2023)
Objective To construct a reliable nomogram available online to predict the postoperative survival of patients with perihilar cholangiocarcinoma. Methods Data from 1808 patients diagnosed with perihilar cholangiocarcinoma between 2004 and 2015 were extracted from the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) database. They were randomly divided into training and validation sets. The nomogram was established by machine learning and Cox model. The discriminant ability and prediction accuracy of the nomogram were evaluated by concordance index (C-index), receiver operator characteristic (ROC) curve and calibration curve. Kaplan-Meier curves show the prognostic value of the associated risk factors and classification system. Results Machine learning and multivariate Cox risk regression model showed that sex, age, tumor differentiation, primary tumor stage(T), lymph node metastasis(N), TNM stage, surgery, radiation, chemotherapy, lymph node dissection were associated with the prognosis of perihilar cholangiocarcinoma patients relevant factors (P < 0.05). A novel nomogram was established. The calibration plots, C-index and ROC curve for predictions of the 1-, 3-, and 5-year OS were in excellent agreement. In patients with stage T1 and N0 perihilar cholangiocarcinoma, the prognosis of ≥ 4 lymph nodes dissected was better than that of 1- 3 lymph nodes dissected (P < 0.01). Conclusion The nomogram prognostic prediction model can provide a reference for evaluating the prognosis and survival rate of patients with perihilar cholangiocarcinoma. Patients with stage T1 and N0 perihilar cholangiocarcinoma have more benefits by increasing the number of lymph node dissection.